Knockdown of Long Non-Coding RNA NEAT1 Inhibits Proliferation and Invasion and Induces Apoptosis of Osteosarcoma by Inhibiting miR-194 Expression - Wang, Heping (Yonsei Med J, 2017)
PURPOSE: Long non-coding RNA (lncRNA) nuclear paraspeckle assembly transcript 1 (NEAT1) has been implicated as an oncogene in the development and progression of osteosarcoma. This study aims to explore the mechanism of NEAT1 in osteosarcoma. MATERIALS AND METHODS: Expressions of NEAT1 and miR-194 in osteosarcoma tissues and cells were detected by quantitative real-time PCR. The effects of NEAT1 knockdown or miR-194 overexpression on cell proliferation, invasion, and apoptosis were determined by 3-[4, 5-dimethylthiazol-2-yl]-2, 5 diphenyl tetrazolium bromide (MTT) assay, transwell invasive assay, and flow cytometry analysis, respectively. Luciferase reporter assay was performed to observe the possible interaction between NEAT1 and miR-194. RESULTS: NEAT1 was upregulated and miR-194 was downregulated in osteosarcoma tissues and cells. Knockdown of NEAT1 or overexpression of miR-194 suppressed proliferation and invasion and induced apoptosis of osteosarcoma cells in vitro. Luciferase reporter assay validated that NEAT1 could interact with miR-194 and negatively modulated its expression. Furthermore, inhibition of miR-194 reversed the suppression of proliferation and invasion and the promotion of apoptosis induced by NEAT1 depletion in osteosarcoma cells. CONCLUSION: Knockdown of NEAT1 suppressed proliferation and invasion and induced apoptosis in osteosarcoma cells by inhibiting miR-194 expression.